Advertisers use online reviews to design more effective advertisements - Rahat Ullah; Ghayur Ahmad; Azaze Azizi Abdul Adis; Atya Zeb (Universidad Nacional Autónoma de México, 2022)
The key advertisement element “text” has a unique effect on advertisements and a number of studies have examined how advertisements need to be effective and persuasive. This paper aims to mine the customer reviews for emotional, non-emotional content to design more effective advertisements. The results suggest that the recall effect is higher for print advertisements containing emotional content. Also, we found that advertisements with a mix of emotional and non-emotional content will have a positive attitude towards the print advertisements. Furthermore, It has been found that viewing advertisements with a mix of both emotional and non-emotional text will increase purchase intension among consumers.